2019 IEEE 10th Annual Ubiquitous Computing, Electronics &Amp; Mobile Communication Conference (UEMCON) 2019
DOI: 10.1109/uemcon47517.2019.8993101
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Blockchains to Support Electronic Health Records for Hospital Systems

Abstract: Electronic Health Records (EHRs) have improved many aspects of healthcare and allowed for easier patient management for medical providers. Blockchains have been proposed as a promising solution for supporting Electronic Health Records (EHRs), but have also been linked to scalability concerns about supporting real-world healthcare systems. This paper quantifies the scalability issues and bottlenecks related to current blockchains and puts into perspective the limitations blockchains have with supporting healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Scalability solutions have already been studied and experimented on, such as Proof-of-Authority and the novel Byzanthine fault tolerance (BFT) consensus mechanisms [ 44 , 56 , 67 ]. Other methods include enhancing the blockchain architecture through tiered-chain [ 40 , 64 ] or side-chain structures [ 57 ]. Although privacy solutions were more limited in our review, we came across one by Reen et al [ 70 ] who proposed storing InterPlantary Naming System records instead of the conventional hash of the medical records directly on the blockchain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scalability solutions have already been studied and experimented on, such as Proof-of-Authority and the novel Byzanthine fault tolerance (BFT) consensus mechanisms [ 44 , 56 , 67 ]. Other methods include enhancing the blockchain architecture through tiered-chain [ 40 , 64 ] or side-chain structures [ 57 ]. Although privacy solutions were more limited in our review, we came across one by Reen et al [ 70 ] who proposed storing InterPlantary Naming System records instead of the conventional hash of the medical records directly on the blockchain.…”
Section: Resultsmentioning
confidence: 99%
“…One of the major areas regarding blockchain PHRs that is still undergoing much research is scalability. We came across a few ideas such as Proof-of-Authority, novel BFT consensus mechanisms, and other modified blockchain architectures such as tiered-chains and side-chains [ 40 , 44 , 56 , 57 , 64 , 67 ]. Apart from blockchain PHR teams working on this, the space may also benefit from parallel innovations from the larger blockchain ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain integrity of data, the proof of integrity is attached to the BC network; to ensure privacy, an access control mechanism was put in place; and for security, a channel formation scheme was used [74] in their approach. Donawa et al [33] identified scalability issues in traditional BC networks of large-scale healthcare systems, which can generate up to 7.5 million medical records per day and proposed a BC-based system capable of handling over 30 million records daily as a solution for the prevailing scalability issue [54]. To achieve this, they proposed a sidechain and the main network to relieve its load and prevent bottlenecking.…”
Section: Patient Data Sharingmentioning
confidence: 99%
“…The main chain performs tasks such as handling the joining/leaving of the patients in the network and produce a discharge summary at the end of the patient visit. Their proposed model can revolve the scalability issue of the BC when dealing with a large amount of transactions [33].…”
Section: Patient Data Sharingmentioning
confidence: 99%
“…With the recent developments in the field of big data, many studies have investigated the storage and management of large amounts of data, such as videos and images, in blockchains in various fields, such as medicine, forensics, and education [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. A permissioned blockchain framework for forensic applications of connected vehicles was proposed in [ 20 ].…”
Section: Related Workmentioning
confidence: 99%